'Pleural Triage' facilitates effective management of a pleural service in the COVID-19 era. (12th December 2021) - Ajmal, Syed; Stockbridge, Alison; Vella, Claire; Johnstone, Sarah; Deakin, Tracey; Tufail, Muhammad; Panchal, Rakesh K
The COVID-19 pandemic has created new challenges for management of pleural diseases. As resources and staff have been redirected to manage acutely unwell COVID-19 patients, routine medical practice and service provision for pleural diseases have been severely disrupted. We recognised the impact this had for patients with pleural diseases, who can be highly vulnerable to infection and often have conditions for which treatment cannot be safely delayed. The pleural service was reviewed in a tertiary centre, focusing on the changes that allowed maintenance of a service whilst maximising patient and staff safety, with the aim that these service transformations can be adopted elsewhere to improve care for pleural patients during and beyond COVID-19.